El monumento al sacrificio de Ricaurte, un dispositivo de memoria demolido en Bogotá (1913-1936) [Estudios] - Martínez Martín, Abel Fernando (2023)
The article studies the creation and demolition of the monument of Antonio Ricaurte, considered a “child hero” in the San Mateo battle, during the independence process in Colombia. The monument was proposed for erection in 1914 and was finally placed in Chapinero, in 1924, in the middle of the tramway tracks that linked that area to Bogota. Just a few years later, the municipal administration decided to demolish the monument to improve urban traffic. The study is framed in the analysis of urban conflicts between modernization and the construction and preservation of memory structures.